PENGARUH KONFLIK AGENSI TERHADAP PROFITABILITAS PERUSAHAAN KELUARGA DENGAN NON-FAMILY AFFILIATED MANAGEMENT SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Keluarga di Bidang Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Chikita Juniarti; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the impact of agency conflicts on family firm’s profitability, which are: 1) the impact of PA conflicts on family firm’s profitability; and 2) the impact of PP conflicts on family firm’s profitability. This research also examines the moderating impact of non-family affiliated management on the initial relationship between each type of agency conflict and family firm’s profitability. The dependent variable that is used in this research is profitability, while the independent variables that are used in this research are PA conflicts and PP conflicts. The number of sample in this research are 192 samples taken from 64 family firms in manufacturing sector that are listed on the Indonesia Stock Exchange during the period of 2016-2018. The data used in this research are secondary data that were selected using purposive sampling method taken from the said firms’ annual reports. The technique of analysis used to examine the hypothesis was OLS regression analysis. The empirical results of this research show that PA conflicts affect family firm’s profitabilty positively, while PP conflicts affect family firm’s profitabilty negatively. The results also show while non-family affiliated management enhances the positive impact of PA conflicts on family firm’s profitability, it has no moderating impact on the initial relationship between PP conflicts and family firm’s profitability.